717 Roux-En-Y Versus Single Loop Reconstruction in Pancreaticoduodenectomy: A Systematic Review and Meta-Analysis. (12th October 2021) - Mobarak, S; Tarazi, M; Davé, M; Varley, R; Stott, M; Baltatzis, M; Satyadas, T
Abstract: Aim: Post-operative pancreatic fistula (POPF) and delayed gastric emptying (DGE) both remain problematic complications following pancreaticoduodenectomy. This systematic review and meta-analysis evaluates whether Roux-en-Y compared to a single loop reconstruction in pancreaticoduodenectomy significantly reduces rates of these complications. Method: A systematic review and meta-analysis were conducted according to the PRISMA guidelines by screening EMBASE, MEDLINE/PubMed, CENTRAL and bibliographic reference lists for comparative studies meeting the predetermined inclusion criteria. Post-operative outcome measures included: POPF, DGE, bile leak, operating time, blood loss, need for transfusion, wound infection, intra-abdominal collection, post-pancreatectomy haemorrhage, overall morbidity, re-operation, overall mortality, hospital length of stay. Pooled odds ratios or mean differences with 95% confidence intervals were calculated using either fixed- or random-effects models. Results: Fourteen studies were identified including four randomized controlled trials (RCTs) and 10 observational studies reporting a total of 2 031 patients. Data synthesis showed no statistically significant difference between the two groups in any of the outcome measures except operating time, which was longer in those undergoing Roux-en-Y reconstruction. Conclusions: Roux-en-Y is not superior to single loop reconstruction in pancreaticoduodenectomy but may prolong operating time. Future high-quality randomized studies with appropriate study design and sample size power calculation may be required to further validate this conclusion.